Harmonizing Revelation and Reason: Theoretical Frameworks for Integrating Islamic Values and Modern Science - Prafitriyani Putri; Ade Irvan; Nadia Arrifqi; Muhammad Ikhlasul Amal; Helmi Syaifuddin (Educazione: Journal of Education and Learning, 2025)
This study aims to analyze the scientific paradigm of integrating Islamic and modern scientific knowledge in Islamic higher education through a literature-based approach. It employs a descriptive qualitative method using systematic analysis of relevant scholarly literature. The findings indicate that the integration concept emphasizes the unity of religious knowledge and contemporary science through a holistic framework based on the philosophy of a cell of knowledge and a house of civilization. This integration contributes to the advancement of Islamic higher education by strengthening the coherence between faith and scientific inquiry and offers implications for developing a more holistic and value-based academic paradigm in Muslim educational contexts. It also provides strategic recommendations for curriculum development, interdisciplinary collaboration, and the strengthening of integrative epistemology to support the sustainability of Islamic higher education transformation in response to global academic challenges. Overall, the study highlights the importance of integrating spiritual values and scientific reasoning as a foundation for future educational innovation and intellectual development within Islamic scholarship in higher education contexts worldwide and continuous improvement.